Employee assistance programme: A workplace intervention for psychological health and sickness absence / Marzuki Isahak - Marzuki, Isahak (2013)
Background: The Employee Assistance Programme (EAP) for stress is an individual approach worksite-based programme to improve psychological health of the workers. However, the scientific evidence on effectiveness of EAP is still controversial. Most EAP providers claim that the EAP gave positive impacts on personal health and work performance. However, records from employers show a contradictory finding based on their sickness absence, worker’s compensation and incomplete work days data. Evidences from Asian countries on this matter were still scarce. In Malaysia, there was no published study on the effectiveness of EAP. Objectives: The objective of this study was to determine the effectiveness of EAP in the improvement of workers psychological health status and sickness absence. Methods: This is a randomised-controlled trial conducted among 150 workers in a public university in Kuala Lumpur. There were 75 participants in both intervention and comparison group respectively. Information on socio-demographic data and self-perceived depression, anxiety and stress using DASS-21 questionnaire was administered at baseline. Biochemical, anthropometry and clinical data were measured pre-intervention. Sickness absence data also was obtained from the Human Resource Department. Psychological work exposures were measured via Job Content Questionnaire (JCQ). EAP interventions given were consisting of stress management workshop, two sessions of individual counselling and relaxation therapy for the period of six months. As for the comparison group, only self-help stress management pamphlet was given to them. All the indicators were repeated in both groups post-intervention. Results: The participants mean ages were 43.0 and 44.2 years old for intervention and comparison group respectively. The majority of participants in both groups were females, Malay ethnicity and in support group of occupational class. The baseline self-perceived psychological symptoms mean score in intervention group were 5.36, 6.35 iv and 7.89 for depression, anxiety and stress respectively. In comparison group, their mean score for self-perceived depression, anxiety and stress were 4.95, 5.87 and 7.59 respectively. There was similar proportion of high job strain of 21.3% in both groups. Both groups showed a baseline sickness absence rate of more than 2 days over 6 months period. After the intervention, there were significant improvement in self-perceived depression (p <0.001), anxiety (p <0.001) and stress (p <0.001) score among intervention group as compared to comparison group. Serum cortisol also showed a significant reduction in intervention group post-intervention (p<0.05). However, all the other biochemical, anthropometry, clinical and sickness absence indicators did not show significant difference after the intervention. As for work psychological exposures, EAP managed to significantly reduce participants’ job demand (p<0.01) and increase co-workers support (p<0.05). Conclusion: EAP for stress has shown to significantly improve self-perceived depression, anxiety and stress symptoms. Our results proved that EAP is effective in Malaysia especially among university workers. Trial Registration: IRCT201102275923N1 Funding: Postgraduate Research Grant, University of Malaya Keywords: Stress Management Programme, Stress, Depression, Anxiety, University.